Artists First, Teachers Second. Issue 6 (2nd November 2019) - Follari, Lissanna; Navaratne, Maria
Abstract : If we can find ways to integrate the arts in education, we will be helping students prepare for the future by giving them opportunities to practice creativity, communication, critical thinking, and collaboration.